METHIMAZOLE-INDUCED APLASTIC ANEMIA WITH CONCOMITANT HEPATITIS IN A YOUNG FILIPINA WITH GRAVES’ DISEASE - Wijaya, Natalia Sisca; Ong-Ramos, Celeste (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Antithyroid drug therapy is essential for treatment of hyperthyroidism. However, its use is not without risks. Agranulocytosis, aplastic anemia and hepatotoxicity are uncommon but potentially serious adverse events reported to occur with patients on these agents. In our review of literature, this is the first case in the Philippines of methimazole-induced aplastic anemia and hepatitis that occurred after starting ATD. CASE A 34-year-old female Filipino with Graves’ disease on methimazole came in due to fever, sore throat and jaundice. She was initially diagnosed with methimazole-induced agranulocytosis and drug-induced liver injury. She was treated with intravenous broad-spectrum antibiotic and granulocyte colony stimulating factor. On day 4 of admission, she developed pancytopenia and was managed as methimazole-induced aplastic anemia. She was started on steroid therapy and received 1 unit of packed red blood cell. The jaundice also increased, hence, she was given ursodeoxycholic acid. On day 9 of admission, with the consideration of"lineage steal phenomenon,"biopsy was done and eltrombopag was started. Patient was discharged stable at 12th hospital day. This case presents 3 rare lifethreatening complications of methimazole namely: agranulocytosis, aplastic anemia and hepatitis. CONCLUSION This case underscores the importance of timely detection and recognition of these rare but dangerous side effects associated with methimazole, as well as the institution of proper therapeutic management to prevent mortality and morbidity. Physicians prescribing these drugs should be aware of these potential complications that can occur at any time irrespective of age, duration of use, and methimazole dose at the first or subsequent exposure.